2018
DOI: 10.1002/pc.24902
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the mechanical and electrical conductivity properties of graphene‐based thermoplastic starch/poly(lactic acid) hybrids

Abstract: Environmentally friendly approaches were followed to develop thermoplastic starch (TPS)/poly(lactic acid) (PLA) extruded hybrids at 70:30 and 30:70 compositions, with the incorporation of reduced graphene oxide at 1.0, 3.0, and 5.0 mass% contents. Glucose was chosen as reagent to reduce graphene oxide (GO) to the rGO sample. Theoretical models predicted that the final location of rGO was at the interface of the components. The adhesion between the polymeric phases in the hybrids, observed by scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…This result denoted the restoration of a large part of the conjugated graphitic structure in the rGO‐g product, by the reduction of GO with glucose. The same GO and rGO‐g samples were recently characterized by other techniques, which confirmed the effectiveness of the glucose‐induced reduction …”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…This result denoted the restoration of a large part of the conjugated graphitic structure in the rGO‐g product, by the reduction of GO with glucose. The same GO and rGO‐g samples were recently characterized by other techniques, which confirmed the effectiveness of the glucose‐induced reduction …”
Section: Resultssupporting
confidence: 57%
“…The same GO and rGO-g samples were recently characterized by other techniques, which confirmed the effectiveness of the glucose-induced reduction. [16] rGO-g was dispersed in ATBC plasticizer and incorporated to the TPS/PLA blend by melt extrusion. The structure and crystallinity of the compression-molded composites were investigated by XRD ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the recent interest in the development of biodegradable materials has attracted increasing attention towards PLA nanocomposites [100]. Table 4 summarizes the very last PLA-graphenic composites prepared by means of melt blending [101][102][103][104][105][106][107][108][109][110][111] and other biodegradable and biocompatible polymers [112][113][114][115][116][117].…”
Section: Biodegradable and Biocompatible Polymersmentioning
confidence: 99%
“…Therefore, understanding the crystallinity of PLA allows for the estimation and modification of its properties . Recent studies indicated improvements in electrical conductivity and flexural strength of crystallized PLA on graphene . Similarly, crystallized PLA possess shape memory attributes with higher storage modulus, which is owing to an ordered lamellar structure of crystallized PLA .…”
Section: Introductionmentioning
confidence: 99%
“…20 Recent studies indicated improvements in electrical conductivity and flexural strength of crystallized PLA on graphene. 21 Similarly, crystallized PLA possess shape memory attributes with higher storage modulus, which is owing to an ordered lamellar structure of crystallized PLA. 22 PLA is biocompatible, however, the sharp nano-walls of graphene could kill bacterial cells, providing antibacterial attributes to PLA-graphene nanohybrid.…”
Section: Introductionmentioning
confidence: 99%